Kesejahtraan Psikologi Pasca Cerai Gugat pada Janda dan Duda - Nurjanis; Salina Binti Nen; Jamiah Binti Manaf; Norhayati Binti Mohd Noor (Journal of Education and Culture, 2025)
Divorce is an event that can have a significant psychological impact on individuals, especially in cases of divorce by lawsuit. Widows and widowers after a divorce by lawsuit often face various psychological challenges, such as stress, loneliness, emotional instability, and adaptation to changes in social and economic roles. This study aims to analyze the psychological well-being of widows and widowers after a divorce by lawsuit by examining aspects of emotional balance, social support, and coping strategies applied in dealing with life after divorce. The research method used is a qualitative approach with in-depth interview techniques involving several participants who have experienced divorce by lawsuit. The findings indicate that the psychological well-being of widows and widowers after a divorce by lawsuit is significantly influenced by social support, economic conditions, and adaptive mechanisms in coping with life changes. Individuals with strong social support tend to have better psychological well-being than those experiencing social isolation. Furthermore, coping strategies such as engagement in social activities, spiritual enhancement, and healthy emotional management have been proven to help improve psychological well-being. This study concludes that the psychological well-being of widows and widowers after a divorce by lawsuit can be improved through adequate social support and adaptive coping strategies. Therefore, interventions involving support from family, the community, and psychological services are necessary to help them lead a more prosperous life after divorce.